The Divine Comedy by Dante, Illustrated, Purgatory, Volume 4 - Dante Alighieri, 1265-1321; Doré, Gustave, 1832-1883; Cary, Henry Francis, 1772-1844 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Divine Comedy by Dante, Illustrated, Purgatory, Volume 4" by Dante Alighieri is a narrative poem begun around 1308 and completed around 1321. This second cantica follows Dante's journey through Purgatory, guided by the Roman poet Virgil. Here, souls undergo penance for the seven deadly sins cleansing love perverted through excess, deficiency, or malice as they ascend Mount Purgatory toward the Garden of Eden. The work explores divine justice and the soul's path toward God through medieval Catholic theology. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Divine_Comedy
Release date is 2004-08-05
Produced by David Widger
Keywords: Epic poetry, Italian -- Translations into English; Italian poetry -- To 1400 -- Translations into English